[Stroke] - Ahlhelm, F; Naumann, N; Haass, A; Grunwald, I; Schulte-Altedorneburg, G; Fassbender, K; Reith, W (2006)
Today stroke represents a major medical and political problem in Western industrial nations. High demands need to be placed on the initial diagnostic work-up and therapeutic treatment to ensure that the patients benefit from the recent advancements achieved in diagnostic and therapeutic fields. According to the motto "time is brain" the clinical examination and imaging have to be performed within 60 min ("door to needle time") so that potential patients can be quickly treated with systemic or intra-arterial lysis. However, it should be taken into consideration that the selection of diagnostic imaging facilities depends on several factors such as infrastructure, the time remaining in the diagnostic window, and the severity of the clinical symptoms.